Socioeconomic and environmental survey for implementing sustainable cacao systems for forest conservation for climate change mitigation and peacebuilding in Colombia - Romero Sánchez, Miguel Antonio; Pérez Marulanda, Lisset; Quintero, Marcela; González, Carolina; Calderón, Victor; Vanegas, Silvia; Rio Duque, Martha Lilia del; Vanegas Cubillos, Martha Cristina; Castro-Nuñez, Augusto Carlos (2022)
The main goal of the baseline survey was to understand and document the current farmers’ socioeconomic and environmental conditions and characterize their farming practices to analyze the enabling conditions and determinants of adoption of promising sustainable land use systems (SLUS) and better management practices in Caquetá and Cesar Colombia. The survey consisted of 14 modules that collected information on socio-demographic and economic characteristics, use of natural resources, characterization of the production system and agroforestry systems, propensity to adopt agricultural practices, dissemination and transfer of technology, peacebuilding, and effects of the COVID-19 pandemic. Methodology: The survey data were collected using Android tablet devices CSPro 6.2 and 6.3 (U.S. Census Bureau 2020). The interview method was face-to-face in Spanish, and it was based on a closed-ended survey questionnaire. The data was collected from January 2021 to August 2021. The duration of each interview was approximately 60 minutes. Participation was voluntary and farmers responded freely, and under prior informed consent.